Peningkatan Motivasi Belajar, Kompetensi dan Wawasan Berpikir Siswa dan Siswi Yayasan Al-Mutakabbir Kabupaten Bogor - Saragih, Muhammad Rizal; Rusdi, Rusdi; Hunein, Hamida; Sadewa, Prima; Nurullah, Mawardi; Hasan, Julian Muhammad; Septiningrum, Liana Dwi; Prasetya, Eka Rima; Soeyatno, Rahmah Farahdita; Sucayono, Sucayono; Sujarwo, Sujarwo; Yudawirawan, Moh. Yuddy (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
The aim of this community service is to increase learning motivation, competence and insight into thinking at the tertiary level for the students of the Al-Mutakabbir Foundation, Bogor Regency. The method of community service is seminars and discussions. The population in this community service activity is 50 people, all of whom are students from the Al-Mutakabbir Foundation, Bogor Regency. The result of this community service is that all participants understand and apply all the material and discussions that occur during the event so that the goals of this service are achieved.